Headlines of Nationalism, Subtexts of Class: Poland and Popular Paranoia, 1989-2009 - Kalb, Don (Anthropologica, 2022)
Recent and diverse authors in anthropology such as Jonathan Friedman, Andre Gingrich, Marcus Banks and Arjun Appadurai have suggested that current globalization processes are associated with emergent nationalist sensibilities and majority mobilizations. They also imply—but do not yet empirically study—that such ideological effects are profoundly class structured. This paper takes their lead in studying the emergence of working-class nationalism in post-socialist Poland. It studies the critical junctions of Polish transition and its class configurations and power balances, and develops a relational and quintessentially anthropological understanding of hegemonic and counter-hegemonic fields under the path-dependent effects of globalization in Eastern Europe. It shows, in a critical dialogue with the recent work on Poland of political scientist David Ost on the Solidarnosc movement, that such nationalist sensibilities and mobilizations are not simply the creation of right wing political contenders who fill the void of what used to be the liberal left, but reflect the key experiences of skilled industrial workers in Poland.